ANALISIS PERSEBARAN USAHA KECIL MENENGAH DI KOTA SUNGAI PENUH - Yossi Lorenza YOSSI LORENZA; Yudi Antomi (JURUSAN GEOGRAFI FIS UNP, 2021)
Abstract This study aims to determine (1) the distribution of the number of small and medium enterprises in Sungai Penuh City (2) the distribution of the number of small and medium enterprises in Sungai Penuh City (3) the production value of small and medium enterprises in Sungai Penuh City. This type of research uses quantitative methods with descriptive analysis. The data analysis technique used is descriptive statistical data analysis to determine the distribution of the number of SMEs, LQ (location quotient) to determine the distribution of the number of SMEs, to analyze the production value indicators of income and capital. The results showed that (1) the distribution of small and medium enterprises in Sungai Penuh City with classifications or classes, low, medium, and high classes spread over Sungai Penuh City (2) distribution of the number of small and medium enterprises in Sungai Penuh City with different distributions- different for each sub-district in Sungai Penuh City from the food and drink (culinary) industry, fashion, education, automotive, agribusiness, internet, others (3) production value with income and capital indicators in accordance with the criteria of Law number 20 of 2008, the most widely used for small businesses, namely a capital of Rp. 50,000,000 - Rp. 100,000,000, for medium-sized business capital, the most widely used capital is Rp. <2,000,000,000.00, on the small business income that earns a maximum of Rp. <300,000,000, while for medium-sized businesses the maximum income is Rp. <2,000,000,000.00.